Primaquine to prevent transmission of falciparum malaria. - White, N (2013)
Falciparum malaria is transmitted by anopheline mosquitoes that have fed on blood containing gametocytes of Plasmodium falciparum. In areas of low malaria transmission, where symptomatic infections contribute substantially to malaria transmission, the use of gametocytocidal drugs reduces the incidence of malaria. Artemisinin-based combination therapies provide high cure rates and substantially reduce gametocyte carriage. Artemisinin resistance in P falciparum lessens overall gametocytocidal activity, which provides a selective pressure to the spread of these resistant parasites. The 8-aminoquinoline compounds possess unique gametocytocidal properties and rapidly sterilise the mature transmissible stages of P falciparum. The addition of one dose of primaquine to artemisinin-based combination regimens could help to counter the spread of artemisinin resistance. Although primaquine is commonly recommended for falciparum and vivax malaria, concerns about drug-related haemolysis frequently prevent its administration. The limited available evidence on transmission-blocking effects of primaquine and its forerunner plasmoquine suggests that doses lower than currently recommended (0.50-0.75 mg base per kg), which would be safer, might still be very effective.